LANGUAGE LEARNING STRATEGIES USED BY DIFFERENT ENGLISH PROFICIENCY STUDENTS OF STATE SENIOR HIGH SCHOOL 3 MALANG - EMANTO, YUANITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
English is one of international languages in the world and mainly used in international forums. Because of its importance, Indonesian government decides to make English as a formal subject in schools. Students are expected to have basic competences in four skills those are listening, speaking, reading, and writing comprehensively to reach functional literate. Students should have strategies to improve their proficiency and skill in English. The aims of this study are to find out (1) how language learning strategies applied by students of 11th grade at State Senior High School 3 Malang (SMAN 3 Malang), and (2) how English proficiency levels relate to the use of language learning strategies by students of 11 grade at SMAN 3 Malang. This study applied quantitative research. This study used Strategy Inventory for(SILL) version 7 (EFL/ESL) by Oxford (1990) translated into Bahasa Language Learning Indonesia as the instrument. The English raport score was used to measure students’s proficiency. This study use descriptive analysis and Pearson Product Moment to investigate the use of language learning strategies and the correlation between language learning strategies and English proficiency. The participants were students of 11th grade at SMAN 3 Malang divided into three different levels of English proficiency; those are high, intermediate and low. The results of this study indicate that students are in medium level meaning that they sometimes use those strategies in learning a language. Students with high English proficiency used most metacognitive strategies while intermediate English Proficiency students used most compensation strategies and low English proficiency students used most affective strategies. The positive correlation was found between high English proficiency students and metacognitive strategies and negative correlation was found between low English proficiency students and memory strategies. Based on these findings, students are suggested to apply more metacognitive strategies and combine other strategies in their learning process. For further researchers, it is recommended to examine the language learning strategies in speaking, writing, reading, or listening through interviews and observations. Further researchers are also suggested to use other theories of language learning strategy in conducting research. Keywords: Language Learning Strategies, English Proficiency